LIBERALIZATION OF MEDICAL PERSONNEL SERVICES TRADE THROUGH THE ASEAN FRAMEWORK AGREEMENT ON SERVICES IN THE MUTUAL RECOGNITION ARRANGEMENT - silitonga, indah Lestari (Universitas Semarang, 2022)
International services trade has become free trade regime. Free trade principles have been freely liberalized by developed countries in obtaining maximum profits regardless of the losses suffered by developing countries. In ASEAN region, whose members are mostly developing countries with the largest potential market in the world, this is certainly a cause for concern. Therefore, ASEAN countries see the need for regulations related to services liberalization in ASEAN region. At the 12th ASEAN Summit in 2007, the ASEAN Services Trade Framework Agreement was formed which acts as the basis for the ASEAN services liberalization known as the AFAS. Indonesia has ratified this agreement through Presidential Decree No.88 of 1995 which declares the AFAS as its national policy. As a follow-up measure, ASEAN passed a negotiation on mutual recognition arrangement known as the MRA whose main objective is to facilitate professional services under the AFAS. Indonesia has ratified The MRA on Dental Practitioners on 26 February 2009. This agreement demands the readiness of a country to prepare ideal infrastructure, legal protection, and adequate quality professional resources. Thus, services trade concerning with dental professional health workers, especially in Indonesia, will be able to compete with partner countries that are more prepared.